PERANCANGAN SISTEM INFORMASI KOPERASI PEGAWAI SMK NEGERI 2 PAYAKUMBUH - Ridho Aulia; Denny Kurniadi (Universitas Negeri Padang, 2019)
The problems of union can arise in various parts of the business process implementedthat are services to members and consumers, financial management, sales management, promotions and other various services, both the main process and supporting one. For service business processes, the union uses social media and other similiar platform. For reporting business processes, it is still carried out in a manual way. To improve the results of the business process in the system of union, it requires web-based e-commerce in order to help all of the aspects. The presence of an e-commerce system is to help promoting the products and facilitate consumers to do everything within the business processes. The design of the e-commerce system uses the MVC (Model, View, Controller). The programming language used is the PHP (PHP Hypertext Preprocessor) based on Codeigniter framework and MySQL as a Database Management System (DBMS) and Sublime Text 3 as the editor. Business processes that exist in this union could sell products in a larger area in order to convey the information about the products to consumers quickly. With the system in the union, consumers will be much easier in ordering the producs they want.Keywords : Codeigniter Framework, MySQL, E-Commerce.